Mitogenome data of Hylobates abbotti Kloss, 1929 (Abbott’s Gray Gibbon) - Nurthaqifah, Samsudin; Jeffrine Rovie, Ryan Japning; Faisal Ali, Anwarali Khan; Azroie, Denel; Melvin, Terry Gumal; Sandy, Ling; Gan, Han Ming (Elsevier Inc., 2025)
Complete mitochondrial genomes provide valuable insights into species identification, accompanied by their respective geographic variation, molecular taxonomy, conservation strategies, and phylogenetic relationships among primates. This data article presents the complete mitochondrial genome sequence of Hylobates abbotti (Abbott’s gray gibbon), a species endemic to southwest Borneo, previously classified as a subspecies of Hylobates muelleri (the Bornean gibbon). The mitogenome is 16,501 base pairs in length, comprising 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and a control region. A phylogenetic tree was constructed using the maximum likelihood (ML) method, offering insights into the evolutionary relationships within the genus Hylobates. The mitogenome has been deposited at GenBank under the accession number PQ867516.